A comparative evaluation of feathers, oropharyngeal swabs, and cloacal swabs for the detection of H5N1 highly pathogenic avian influenza virus infection in experimentally infected chickens and ducks. (November 2015) - Nuradji, Harimurti; Bingham, John; Lowther, Sue; Wibawa, Hendra; Colling, Axel; Long, Ngo Thanh; Meers, Joanne
Oropharyngeal and cloacal swabs have been widely used for the detection of H5N1 highly pathogenic avian Influenza A virus (HPAI virus) in birds. Previous studies have shown that the feather calamus is a site of H5N1 virus replication and therefore has potential for diagnosis of avian influenza. However, studies characterizing the value of feathers for this purpose are not available, to our knowledge; herein we present a study investigating feathers for detection of H5N1 virus. Ducks and chickens were experimentally infected with H5N1 HPAI virus belonging to 1 of 3 clades (Indonesian clades 2.1.1 and 2.1.3, Vietnamese clade 1). Different types of feathers and oropharyngeal and cloacal swab samples were compared by virus isolation. In chickens, virus was detected from all sample types: oral and cloacal swabs, and immature pectorosternal, flight, and tail feathers. During clinical disease, the viral titers were higher in feathers than swabs. In ducks, the proportion of virus-positive samples was variable depending on viral strain and time from challenge; cloacal swabs and mature pectorosternal feathers were clearly inferior to oral swabs and immature pectorosternal, tail, and flight feathers. In ducks infected with Indonesian strains, in which most birds did not develop clinical signs, all sampling methods gave intermittent positive results; 3–23% of immature pectorosternal feathers were positive during the acute infection period; oropharyngeal swabs had slightly higher positivity during early infection, while feathers performed better during late infection. Our results indicate that immature feathers are an alternative sample for the diagnosis of HPAI in chickens and ducks.